Aesthetic of Facial Allusions in the Poetries of (Jamal Sharbazhery and E H B) (Raparin Journal of Humanities (RJH), 2023)
Aesthetic of Facial Allusions in the Poetries of (Jamal Sharbazhery and E H B))The process of communication and transferring knowledge via language allusion cannot be successful alone rather it needs non-linguistic reference to develop the communication. This significant role is the same in literature field as well. One of the non-linguistic reference is facial expression, so interpreting and analyzing any gesture and facial expression have its meaning and message. Though, it has a great role in literature particularly in poetical texts. Embodiment of facial gestures in poetry will contribute the shortness, purifying and aesthetic of the poetry which is the historical characteristics of poetry. Both poets ( Jamal Sharbazhery and E H B) embioment the facial expressions in their poetries successfully, so they were significant basics of aesthetics of the poetries. In most cases the gestures and facial expressions more attracts both poets and they were under the influence of gestures and facial expressions.